Legal Regulation of International Contradictions in the Modern International Migration Processes - Rybin, Danil Veycheslavovich; Mishalchenko, Yury Vladimirovich; Polunina, Anastasia Viktorovna; Rusetskiy, Mikhail Gennad’evich (Journal of History Culture and Art Research, 2019)
The article is devoted to the issues of legal regulation of international contradictions in the modern international migration processes. Special attention is given to the international legal acts for human rights and citizens’ protection in the sphere of international migration. The authors consider international and national legal mechanisms for the protection of migrants’ rights. New approaches to solving the problems of migrants’ rights protection under the conditions of population’s increasing mobility and globalization are offered. Special attention is paid to legal regulations of the United Nations. The authors consider the controversies associated with the adoption of the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families by the states in which the number of emigrants far exceeds the influx of arriving migrants and by the developed countries that have not signed or ratified the Convention.